Low-Pressure Argon/Hydrogen/Oxygen Plasma Treatment on LiMn2O4 Li-Ion Hybrid Supercapacitors. (1st April 2023) - Chen, Hong-Kai; Ni, I-Chih; Wu, Chih-I; Cheng, I-Chun; Chen, Jian-Zhang
Abstract : LiCl + Mn(NO3 )2 ·4H2 O pastes are screen-printed on a carbon cloth substrate and then calcined at 400 °C for 6 h in a tube furnace to convert them into LiMn2 O4 . Ar, Ar+5%H2, or Ar+5%O2 low-pressure plasma is then used to treat the LiMn2 O4 /carbon cloth. The treated LiMn2 O4 /carbon cloth is then used as the electrode for a Li-ion hybrid supercapacitors (Li-HSCs) with a three-electrode configuration in 1-M Li2 SO4 liquid electrolyte. Ag/AgCl and Pt electrodes were used as reference and counter electrodes, respectively. Li-HSCs are characterized by galvanostatic charging/discharging, cyclic voltammetry, and electrochemical impedance spectroscopy. The results indicate that plasma treatment improves the Li-HSCs performance. In particular, Ar+5%O2 plasma treatment increases the areal capacity by ∼24% to 23.12 μ A h cm −2 . It also improves the coulomb efficiency and capacity retention rate of LiMn2 O4 Li-HSCs.